"Other People's Battles"? Incorporating the Experiences of Immigrant-Origin Black American Youth in Ethnic/Racial Identity Research. Issue 2 (3rd April 2022) - Agi, Abunya C.; Rivas-Drake, Deborah
ABSTRACT: In this theoretical article, we illuminate the ways in which the ethnic/racial identity literature to date is limited in its ability to fully capture the diverse experiences of Black youth in the U.S. and Canada. Specifically, despite representing a growing share of the Black population, the experiences of immigrant-origin Black youth (at least one parent born outside the U.S./Canada) are often overlooked and undertheorized in ethnic/racial identity research. We draw from the phenomenological variant of ecological systems theory, intersectional invisibility framework, and the theory of multiplicity to highlight conceptual and methodological gaps in the way ethnic/racial identity is studied among Black youth. Accounting for the detrimental impact of negative stereotypes, racial discrimination, and xenophobia, we unpack the unique process of ethnic/racial identity development for immigrant-origin Black youth. We then apply acculturation theory to address the limitations in ethnic/racial identity findings. We conclude with recommendations to clarify inclusion criteria when using the term African American and to report on Black youth's ethnic diversity.